2011
DOI: 10.4103/0971-6203.75471
|View full text |Cite
|
Sign up to set email alerts
|

Radiation safety concerns and diagnostic reference levels for computed tomography scanners in Tamil Nadu

Abstract: Radiation safety in computed tomography (CT) scanners is of concern due its widespread use in the field of radiological imaging. This study intends to evaluate radiation doses imparted to patients undergoing thorax, abdomen and pelvic CT examinations and formulate regional diagnostic reference levels (DRL) in Tamil Nadu, South India. In-site CT dose measurement was performed in 127 CT scanners in Tamil Nadu for a period of 2 years as a part of the Atomic Energy Regulatory Board (AERB)-funded project. Out of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Also, the third quartile value of CTDI v for abdomen scan is less than the one reported for Tamil Nadu (521 mGy). [ 14 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the third quartile value of CTDI v for abdomen scan is less than the one reported for Tamil Nadu (521 mGy). [ 14 ]…”
Section: Resultsmentioning
confidence: 99%
“…An attempt has been made in the year 2008 to determine the third quartile value for CTDI v for the CT scanners in Tamil Nadu and the values were reported as 557 and 551 mGy for thorax and abdomen procedures, respectively. [ 14 ] Since then no studies have been carried out in this line in India. The aim of the present study is to establish DRL for CTDI v and DLP for the CT scanners operating in Pudhuchery region.…”
Section: Introductionmentioning
confidence: 99%
“…There were many countries in Western and Asian regions that have established and reported their national DRLs for adult CT studies: for example Australia, Northern Greece, Turkey, the United Kingdom (UK), other European countries, US, Iran, Malaysia, Japan, and India. [15][16][17][18][19][20][21][22][23][24][25] A study in Thailand in 2012 found CT radiation dose of head below international DRLs but those of CT chest and abdomen exceeded the international DRLs. 26 A 2011's study at five Thai university hospitals, including Songklanagarind Hospital, noted DRLs of adult brain, chest and abdominal CT varied widely but were within acceptable levels compared to international DRLs.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there is enough recently published regional CT radiation dose data from south India,[ 15 16 17 18 ] any such data have not considered the make of CT equipment (number of slices of CT) and actual number of phases in contrast CT examinations. These factors are important with regard to actual dose delivered to the patient.…”
Section: Introductionmentioning
confidence: 99%